Transparency, Accountability, and Competence of Village Apparatus toward the Management of Village Revenue and Expenditure Budget (APBDes): A Study in Jeneponto Regency - Basri Bado; Fitriani Fitriani; Inanna Inanna; Najamuddin Najamuddin (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2025)
This study aims to evaluate the influence of transparency, accountability, and competence of village officials on the management of the Village Revenue and Expenditure Budget (APBDes) in Jeneponto Regency. A quantitative approach was used with an analysis of the relationship between variables. Data were collected through the distribution of 60 questionnaires to village officials, and analyzed using the Partial Least Square - Structural Equation Modeling (PLS-SEM) method through the SmartPLS application version 4.1.0.8. The results showed that transparency (p = 0.000), accountability (p = 0.002), and competence of village officials (p = 0.000) had a significant effect on the management of the APBDes. These findings provide an important contribution to policy formulation, particularly in improving the quality of public services and the effectiveness of village fund management, including in the village transportation sector. By strengthening transparency, accountability, and the competence of village officials, village governments can achieve more efficient and responsive budget management to community needs, including in the development of equitable and sustainable transportation infrastructure. Practically, these results can serve as a reference for policymakers and village technical implementers in designing strategies to increase the capacity of village officials. Academically, this research enriches the literature on public financial governance at the village level with a quantitative approach based on PLS-SEM.